Prevalence of bat viruses associated with land-use change in the Atlantic Forest, Brazil - Loh, Elizabeth H.; Nava, Alessandra; Murray, Kris A.; Olival, Kevin J.; Guimarães, Moisés; Shimabukuro, Juliana; Zambrana-Torrelio, Carlos; Fonseca, Fernanda R.; de Oliveira, Daniele Bruna Leal; Campos, Angélica Cristine de Almeida; Durigon, Edison L.; Ferreira, Fernando; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Viruses that originate in wildlife are key threats to global health, and their emergence is often associated with anthropogenic factors, including land-use change. However, few studies have assessed how host communities and their viruses alter with land-use change, particularly in highly biodiverse sites. We investigated the effects of deforestation on bat abundance and diversity, and viral prevalence across five forested sites and three nearby deforested sites in the interior Atlantic Forest of southern Brazil. Nested-PCR and qPCR were used to amplify and detect viral genetic sequence from six viral families (corona-, adeno-, herpes-, paramyxo-, hanta-, and astro-viridae) in 944 blood, saliva and rectal samples collected from 335 bats. We found that deforested sites had a less diverse bat community than forested sites, but higher viral prevalence and diversity after controlling for confounding factors. Our findings suggest that deforestation can result in reduced bat diversity and increased abundance of generalist synanthropic species, and that these host higher viral diversity and prevalence. Although not measured in this study, a higher human-animal contact rate with bat hosts harboring elevated viral prevalence and diversity could combine to increase disease emergence risk in human-modified landscapes.